Redundant Group Agency. Issue 5 (September 2019) - Moen, Lars J. K.
According to group-agent realism, treating groups as agents with their own intentional states, irreducible to those of the group members, helps us explain and predict the groups' behavior. This paper challenges this view. When groups judge logically interconnected propositions, group members often have incentives to misrepresent their beliefs concerning propositions they care less about in order to increase the probability of their groups adopting their view of propositions they consider more important. Aggregating such untruthful judgments may lead to the group forming false beliefs. Treating groups as agents will then not help us explain or predict their behavior.